2021
DOI: 10.1016/s2468-2667(20)30291-7
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation and risk of heart disease and stroke: analysis of two large UK prospective studies

Abstract: Summary Background Social isolation has been associated with increased risk of coronary heart disease and stroke. However, it is unclear whether the associations differ between fatal and non-fatal events or by the type of isolation (living alone or having few social contacts). We aimed to examine these associations in two large UK prospective cohorts. Methods Million Women Study and UK Biobank participants without previous coronary heart disease or stroke w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 23 publications
3
56
0
Order By: Relevance
“…We found the education did not modify the associations of social isolation with mortality, which was not consistent with previous studies showing the mortality risk of social isolation change depend upon SEP but without clarifying the types of social contact [ 27 , 59 , 60 ]. Moreover, living alone was particularly increased the CVD mortality in unhealthy participants suggesting the importance of immediate help among people who live alone, as a recent study reported [ 3 ].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We found the education did not modify the associations of social isolation with mortality, which was not consistent with previous studies showing the mortality risk of social isolation change depend upon SEP but without clarifying the types of social contact [ 27 , 59 , 60 ]. Moreover, living alone was particularly increased the CVD mortality in unhealthy participants suggesting the importance of immediate help among people who live alone, as a recent study reported [ 3 ].…”
Section: Discussionmentioning
confidence: 84%
“…For example, the UK Biobank study [ 32 ] assessed social isolation using a social isolation index, which only included questions on face-to-face contact. The Million Women Study [ 3 ] and English Longitudinal Study of Ageing [ 54 ] included results of a composite score with e-mail, phone and face-to-face contact but did not report results on different isolation types. The Whitehall II Study [ 55 ], the Nurses’ Health Study [ 56 ], and the Heinz Nixdorf Recall Study [ 24 ] also showed a higher mortality risk related to social isolation but did not specify the types of contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loneliness has been a growing topic of interest in Europe over the last decade [ 1 – 4 ], as it has been shown to be linked with ill health and to increase with age. Loneliness is correlated with a higher risk of developing mental conditions (e.g., depression, dementia) and a deterioration in physical health (e.g., less active lifestyles, diabetes, stroke, coronary heart disease), as shown for instance in [ 5 11 ]. Loneliness is also linked with all causes of mortality [ 12 15 ] and has an impact on health care utilization [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous research ( Guo et al, 2021 ; Smith et al, 2021 ), the social isolation index used in our study was constructed from three questions: 1) Including yourself, how many people are living together in your household (1 point was given for living alone); 2) how often do you contact (e.g. phone, meet, email) family members (1 point was given for answering about rarely or never, monthly, or no family outside household); 3) which of the following (e.g.…”
Section: Methodsmentioning
confidence: 99%